Varieties of Clientelism: Machine Politics during Elections. Issue 2 (28th October 2013) - Gans‐Morse, Jordan; Mazzuca, Sebastián; Nichter, Simeon
<x xml:space="preserve">Abstract</x> Although many studies of clientelism focus exclusively on vote buying, political machines often employ diverse portfolios of strategies. We provide a theoretical framework and formal model to explain how and why machines mix four clientelist strategies during elections: vote buying, turnout buying, abstention buying, and double persuasion. Machines tailor their portfolios to the political preferences and voting costs of the electorate. They also adapt their mix to at least five contextual factors: compulsory voting, ballot secrecy, political salience, machine support, and political polarization. Our analysis yields numerous insights, such as why the introduction of compulsory voting may increase vote buying, and why enhanced ballot secrecy may increase turnout buying and abstention buying. Evidence from various countries is consistent with our predictions and suggests the need for empirical studies to pay closer attention to the ways in which machines combine clientelist strategies.